Tri muhe na en mah – pouk tujega jezika na prostem in senzibiliziranje za okolje - Lipavic Oštir, Alja (Pedagoška perspektiva, 2025)
Understanding the world through compartmentalization into school subjects can be overcome by combining foreign language instruction with an outdoor learning approach and by developing environmental awareness. This places the foreign language in a new, authentic role. Environmental awareness gains significance, as outdoor learning always begins directly from our surroundings, making phenomena related to the environmental crisis more concrete and localized. This is highly valuable in today’s world. The outdoor learning approach itself gains added value when it is connected with classroom instruction, thereby overcoming the common perception that outdoor lessons are merely a form of leisure that takes time away from achieving subject-specific goals. With the OLGEA model, we have demonstrated the opposite – hitting three birds with one stone is indeed possible, provided that we, as teachers, are open to teamwork, interdisciplinary collaboration, and our own learning, which is beneficial for our professional development.
Keywords: environmental awareness; foreign language; interdisciplinary integration; medpredmetno povezovanje; outdoor learning; pouk zunaj; senzibiliziranje za okolje; tuji jezik